Management of Higher Education Development: Conceptual Foundations and Analytical Management Models - Ivanova O. E., Shapovalova O. F. (Law, Economics and Management, 2022)
In recent decades, there have been significant changes in management in general, and in particular in the management of education, which is associated with such processes as globalization, commercialization, public sector reforms and the emergence of the knowledge economy and society. The article discusses the main theoretical approaches developed by researchers in recent years, including the main models of management of the development of higher education. It is concluded that the applicability of a particular management model in countries is determined by the role and place of the education system in them, the historically established interaction of the education system and society. None of the considered models makes it possible to identify its advantages over other models, therefore, the development of education management models needs further development.
Keywords: высшее образование; управление образованием; higher education; management tools; инструменты управления; модели управления; треугольник координации; management models; coordination triangle; education management